PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS SISWA KELAS V SEKOLAH DASAR - Ningrum, Novita Cahya; Alindra, Afrihda Laily; Caturiasari, Jennyta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students conceptual understanding of social science (IPS) subjects by implementing the Project Based Learning (PjBL) learning model at SDN 1 Munjuljaya. This study used Classroom Action Research (CAR) in accordance with the model according to Kemmis and McTaggart which consists of four stages, namely: 1) planning, 2) implementation, 3) observation, and 4) reflection. This study was conducted in two cycles and each cycle consisted of two meetings. The subjects in this study were class VB students of SDN 1 Munjuljaya consisting of 15 male students and 10 female students. The data collection technique used a test, namely by conducting a learning evaluation at the end of the cycle. Then the data analysis technique was carried out using quantitative analysis which was carried out to process the average value of student learning outcomes obtained from the evaluation of each cycle. The results of this study indicate an increase in students conceptual understanding of the cognitive aspect in social science subjects by implementing the Project Based Learning (PjBL) model. In cycle I, the average student score was 69.52% with classical learning completion of 56%, then increased in cycle II to 80.01% with classical completion of 88%. In addition, an increase was also seen in all indicators of conceptual understanding based on Bloom's Taxonomy according to Krathwohl in the cognitive aspect of levels C1 to C6. These results prove that the use of the Project Based Learning (PjBL) model is effective in improving understanding of the concept of science and developing students abilities in collaborating, communicating, and critical thinking.